Vascular Surgery is An Unattractive Career Option for Current Basic Surgical Trainees: A Regional Perspective - Currie, S (The Royal College of Surgeons of England, 2007)
INTRODUCTION: The workload of vascular services will substantially increase in the foreseeable future with the recent changes in surgical training presenting a challenge to training and recruitment in vascular surgery. This study aimed to determine the current feelings towards vascular surgery as a career choice from basic surgical trainees (BSTs) within a single region. MATERIALS AND METHODS: BSTs from a single region were questioned. Probable career specialty choice was ascertained, as were suggestions for changes to the career pathway of a vascular surgeon to make it a more attractive career choice. RESULTS: Seventy-seven of 110 BSTs returned the questionnaire. Of the 77, 52 had previous experience of a vascular firm. Ten BSTs had been on a pure vascular firm as an SHO and 52 had been on a general surgical firm. No BST specified vascular surgery as their ultimate career choice. Career choices included general surgery (n = 30), orthopaedics (n = 17), plastic surgery (n = 9) and urology (n = 5). Thirty-three BSTs would not be tempted at all to a career in vascular surgery. Changes in the career structure that would result in BSTs contemplating a career in vascular surgery included the inclusion of endovascular surgery (n = 13), no compulsion to undertake a period of research (n = 5), pure vascular training (n = 2), more general surgical training (n = 2) and less onerous on-calls when older (n = 2). CONCLUSIONS: The lack of trainees wishing to become vascular surgeons is of grave concern. Increasing the endovascular capabilities of vascular surgeons as well as altering the stance on research may have an increasingly positive role in recruitment.